2018 IEEE Global Communications Conference (GLOBECOM) 2018
DOI: 10.1109/glocom.2018.8647881
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Optimization of LPWA IoT Networks: A Stochastic Geometry Approach

Abstract: Leveraging grant-free radio access for enabling lowpower wide-area (LPWA) Internet of Things (IoT) connectivity has attracted lots of attention in recent years. Regarding lack of research on LPWA IoT networks, this work is devoted to reliability modeling, battery-lifetime analysis, and operation-control of such networks. We derive the interplay amongst density of the access points, communication bandwidth, volume of traffic from heterogeneous sources, and quality of service (QoS) in communications. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…They are representative of realistic networks with devices densely clustered 49 in buildings or shopping centers [70]. First, we observe that OPT-DELTA is able to find the optimal solution within a short time for such large networks.…”
Section: Summary Of Resultsmentioning
confidence: 86%
“…They are representative of realistic networks with devices densely clustered 49 in buildings or shopping centers [70]. First, we observe that OPT-DELTA is able to find the optimal solution within a short time for such large networks.…”
Section: Summary Of Resultsmentioning
confidence: 86%
“…The work presented in the paper builds-up on the conference works presented in [15,47]. In particular, the initial version of the reliability analysis for GFA, without considering replica transmissions and combining (in contrast to this version), was presented in [47].…”
Section: Contributionsmentioning
confidence: 99%
“…The work presented in the paper builds-up on the conference works presented in [15,47]. In particular, the initial version of the reliability analysis for GFA, without considering replica transmissions and combining (in contrast to this version), was presented in [47]. Leveraging carrier frequency offset (CFO) for collision decoding was presented in [15], assuming channel-inversion power-control for IoT devices and a constant number of replica transmissions per packet.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that the proposed approach delivers superior results for backlogged and dynamic scenarios, even if the number of transmitters is large. Another approach was proposed in [67] for mitigating interferences, in which a tractable analytical model for large-scale heterogeneous IoT networks was designed. This approach utilizes a Poisson cluster process (PCP) approach, which takes the correlations among the device locations into account.…”
Section: Literature Reviewmentioning
confidence: 99%